2017
DOI: 10.1111/jpc.13444
|View full text |Cite
|
Sign up to set email alerts
|

Children with motor impairment related to cerebral palsy: Prevalence, severity and concurrent impairments in China

Abstract: Gender, multiple births and family adults with CP were significantly associated with CP-related motor impairment in Chinese children. Proportions of CP and concurrent impairments that increased with severity of motor impairment were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The present results yielded a peak CP prevalence of 2.8 per 1000 children, which is similar to those reported in a previous meta-analysis for a specific age range [ 3 ] but higher than those of other surveys in the Chinese population. The prevalence of CP in China and Hong Kong was reported to be from 1.3 to 1.6 per 1000 children [ 13 15 ], which is lower than that in other developed countries. However, our present findings based on the entire population of Taiwan provide new evidence that Chinese children do not have a lower CP risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results yielded a peak CP prevalence of 2.8 per 1000 children, which is similar to those reported in a previous meta-analysis for a specific age range [ 3 ] but higher than those of other surveys in the Chinese population. The prevalence of CP in China and Hong Kong was reported to be from 1.3 to 1.6 per 1000 children [ 13 15 ], which is lower than that in other developed countries. However, our present findings based on the entire population of Taiwan provide new evidence that Chinese children do not have a lower CP risk.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the United States have reported that Asian children had a lower CP prevalence than Caucasian [ 11 , 12 ]. Furthermore, surveys in China and Hong Kong have reported that the prevalence of CP was 1.3 to 1.6 per 1000 children, which is lower than that in Western countries [ 13 15 ]. However, it is unclear whether the lower prevalence of CP in Asian children can be attributed due to ethnic disparities.…”
Section: Introductionmentioning
confidence: 99%
“…All these tests were negative. Additionally, the parameters of hUCB-MSC vitality, and biological characteristics were tested to meet with International Society for Cellular Therapy standards 19 and documented in test reports for each batch of cell product, including morphology, cell count (5× 10 7 cell/mL, range 90% to 120%, and 1 mL/vial), viability rate (≥90%), cell surface markers, colony-forming ability, differential capacity, and so on. Regarding the cell surface markers, it was found that CD90, CD73, CD105, and CD29 were higher than 95%, and CD45, CD34, CD79a/ CD19, CD14, and HLA-DR were less than 2%.…”
Section: Methodsmentioning
confidence: 99%
“…For mild, moderate, severe, and extremely severe groups of motor impairment, weighted proportions of CP are 14.12%, 20.35%, 27.44%, and 38.09%, respectively. Weighted proportions of concurrent visual, hearing, and cognitive impairment are 5.00%, 6.98%, and 71.06%, respectively 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, both the sensory and motor functions of these persons should be evaluated to gain better understanding of CP. It has been reported that visual and hearing impairments are associated with severity of motor function (Beckung et al, 2008;He, Chen, Wang, Guo, & Zheng, 2017).…”
Section: Introductionmentioning
confidence: 99%